VD_FINDINFO HC / 2012 / 500 vom 16. Juli 2012 - VD Tribunal cantonal (2012)
DÉCISION SUR FRAIS, FRAIS JUDICIAIRES, RETRAITVOIE DE DROIT | 110 CPC (CH), 241 CPC (CH), 319 let. b ch. 1 CPC (CH), 11 TFJC (2010), 27 TFJC (2010)